2016
DOI: 10.1371/journal.pone.0161057
|View full text |Cite
|
Sign up to set email alerts
|

Polymyxin B Nephrotoxicity: From Organ to Cell Damage

Abstract: Polymyxins have a long history of dose-limiting toxicity, but the underlying mechanism of polymyxin B-induced nephrotoxicity is unclear. This study investigated the link between the nephrotoxic effects of polymyxin B on renal metabolic functions and mitochondrial morphology in rats and on the structural integrity of LLC-PK1 cells. Fifteen Wistar rats were divided into two groups: Saline group, rats received 3 mL/kg of 0.9% NaCl intraperitoneally (i.p.) once a day for 5 days; Polymyxin B group, rats received 4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 49 publications
2
34
0
1
Order By: Relevance
“…In a recent in vitro study, Vattimo et al investigated the PMB nephrotoxic effect at the cellular level and demonstrated that PMB renal toxicity is characterized by mitochondrial dysfunction and free radical generation in a pig proximal tubular epithelial cell line (immortalized LLC-PK1 cells) and in rat kidneys (19). The authors of this study also reported a reduced percentage of viable cells in response to higher PMB concentrations, which confirmed the concentration-dependent toxicity of PMB.…”
Section: Discussionsupporting
confidence: 72%
“…In a recent in vitro study, Vattimo et al investigated the PMB nephrotoxic effect at the cellular level and demonstrated that PMB renal toxicity is characterized by mitochondrial dysfunction and free radical generation in a pig proximal tubular epithelial cell line (immortalized LLC-PK1 cells) and in rat kidneys (19). The authors of this study also reported a reduced percentage of viable cells in response to higher PMB concentrations, which confirmed the concentration-dependent toxicity of PMB.…”
Section: Discussionsupporting
confidence: 72%
“…Pulmonary delivery of polymyxins has offered a great promise for the treatment of lung infections (13,14) caused by MDR Gram-negative pathogens, as intravenous administration leads to poor drug disposition at the infection site (7) and nephrotoxicity can occur in up to 60% of patients (9)(10)(11). However, the mechanism of polymyxin-associated pulmonary toxicity has not been examined.…”
Section: Discussionmentioning
confidence: 99%
“…Polymyxin antibiotics have previously been hypothesized to mediate adverse effects via overproduction of ROS (31). We measured ROS production in 2-D-cultured PTECs in response to increasing concentrations of PMB exposure using both CellROX (a free radical sensor that fluoresces when oxidized by ROS) and MitoSOX (a fluorogenic dye that detects intracellular mitochondrial superoxide).…”
Section: Resultsmentioning
confidence: 99%